Rabies virus glycoprotein serology ELISA for measurement of neutralizing antibodies in sera of vaccinated human subjects - Zhao, Rongqing; Yu, Pengcheng; Shan, Yi; Thirumeni, Nagarajan; Li, Maohua; Lv, Yanli; Li, Jianli; Ren, Wenlin; Huang, Lisong; Wei, Jingshuang; Sun, Yufei; Zhu, Wuyang; et al. (Vaccine, 2019)
•First serology ELISA based on recombinant RABV GP for measurement of virus neutralizing antibodies.•Manufacturing and assay protocol are well-standardized with reliable production and test data.•The specificity and sensitivity of ELISA are 100% and 91.1% when benchmarked with the RFFIT method.•The ELISA offers a simple, cost-effective and rapid tool to assess the effectiveness of vaccination. Vaccination provides protection against infection by inducing VNAs mainly against RABV surface GP. The measurement of VNAs to RABV is commonly used to assess the level of immunity in humans and animals after vaccination. A VNA titer of  ≥ 0.5 IU/mL of sera indicates adequate response to vaccination. Here, we report the development and validation of a RABV GP serology ELISA kit for semi-quantitative measurement of VNA titers in sera of vaccinated human subjects. Using a recombinant RABV GP expressed in mammalian cells as the capture antigen, the ELISA method was established using HuMAb NM57 reference initially and HRIG reference subsequently. The limit of detection (LOD), linear range, reproducibility, and precision of the method were examined. Specificity and sensitivity were established to assess the diagnostic accuracy. RABV GP for ELISA plate coating and optimal dilution of human serum sample was 1 µg/mL and 1:20, respectively. Multiple assays were carried out by different technicians at different laboratories for assay standardization. Using the HRIG reference, the LOD was found to be 0.02–0.06 IU/mL and the linear range was 0.2–10.0 IU/ mL. The inter-assay CVs were in the range of 6.60–10.79%, indicating the reproducibility. None of the 12 known negative human sera, tested positive by ELISA, highlighting the specificity. A total of 415 unknown positive human sera were double-blind tested by the RFFIT and ELISA. The VNA titer cut-off value of ELISA was set at 1.5 IU/mL to ensure no false-positive. The diagnostic specificity and sensitivity were 100% and 91.1%, respectively. The validation data characterize this ELISA as a suitable method for semi-quantitative measurement of VNA titers in human serum samples to assess vaccination status. The ELISA kit can offer simplicity, speed, low cost and high throughput, making it a practical tool for monitoring the immune response following vaccination.